Generalized Adaptive Backstepping Synchronization for Non-Identical Parametrically Excited Systems - Idowu, B. A. A.; Vincent, U. E. E.; Njah, A. N. N. (Nonlinear Analysis: Modelling and Control, 2009)
In this paper, we investigate the synchronization of chaotic systems consisting of non-identical parametrically excited oscillators. The backstepping design, which is a recursive procedure that combines the choice of a Lyapunov function with the design of a controller is generalized and employed so as to achieve global chaos synchronization between a parametrically excited gyroscope and each of the parametrically excited pendulum and Duffing oscillator. Numerical simulations are implemented to verify the results.